Microvascular complications and diabetic retinopathy: recent advances and future implications - Barot, Megha (2013)
Retinal microvascular alterations have been observed during diabetic retinopathy (DR) due to the retinal susceptibility towards subtle pathological alterations. Therefore, retinal microvascular pathology is essential to understand the nature of retinal degenerations during DR. In this review, the role of retinal microvasculature complications during progression of DR, along with recent efforts to normalize such alterations for better therapeutic outcome, will be underlined. In addition, current therapeutics and future directions for advancement of standard treatment for DR patients will be discussed.